2018
DOI: 10.1194/jlr.m079731
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate activation of ERM contributes to vascular calcification

Abstract: Vascular calcification is the deposition of mineral in the artery wall by vascular smooth muscle cells (VSMCs) in response to pathological stimuli. The process is similar to bone formation and is an independent risk factor for cardiovascular disease. Given that ceramide and sphingosine 1-phosphate (S1P) are involved in cardiovascular pathophysiology and biomineralization, their role in VSMC matrix mineralization was investigated. During phosphate-induced VSMC mineralization, endogenous S1P levels increased acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…We did this using active Ras pull-down assays as decreased Ras activation is a well-accepted read-out for this inhibitor ( S1 Fig ). Next, we investigated the effects of FTI-277 on the osteogenic differentiation and mineralization of VSMC by using a well-established in vitro model of vascular calcification in which confluent cells are incubated in the presence of βGP [ 17 , 18 , 20 , 21 ]. These studies demonstrated that FTI-277 prevents the βGP-induced increase in the mRNA expression of the osteogenic transcription factors Runx2 ( Fig 1A ) and Msx2 ( Fig 1B ) , reduces the βGP-induced decrease in αSMA mRNA expression ( Fig 1C ) and significantly increases the mRNA levels of matrix Gla protein (an inhibitor of mineralization [ 26 ]) ( Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did this using active Ras pull-down assays as decreased Ras activation is a well-accepted read-out for this inhibitor ( S1 Fig ). Next, we investigated the effects of FTI-277 on the osteogenic differentiation and mineralization of VSMC by using a well-established in vitro model of vascular calcification in which confluent cells are incubated in the presence of βGP [ 17 , 18 , 20 , 21 ]. These studies demonstrated that FTI-277 prevents the βGP-induced increase in the mRNA expression of the osteogenic transcription factors Runx2 ( Fig 1A ) and Msx2 ( Fig 1B ) , reduces the βGP-induced decrease in αSMA mRNA expression ( Fig 1C ) and significantly increases the mRNA levels of matrix Gla protein (an inhibitor of mineralization [ 26 ]) ( Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…VSMC were plated in 6-well plates at 2 x 10 4 cells / cm 2 and maintained in 10% FCS-DMEM until confluent (day 0). At this point, the cells were cultured in 10% FCS-DMEM containing β-glycerophosphate (βGP, 3–5 mM [ 17 , 18 , 20 , 21 ]) and either FTI-277 (1–20 μM), manumycin A (10 or 20 μM), SH6 (Akt inhibitor, 10 μM) or combinations thereof for up to 12 days; control cells were incubated with βGP but with vehicle. Additional controls included cells incubated in 10% FCS-DMEM plus vehicle but without βGP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris et al determined the role of ezrin-radixin-moesin (ERM) proteins as important downstream effectors of sphingosine-1-phosphate (S1P)-induced VSMC matrix mineralization in vitro. The study used pharmacological inhibitors such as desipramine for the inhibition of acid sphingomyelinase (ASM) and ceramidase to elucidate the role of sphingolipids in vitro, but lacking genetic manipulations and in vivo animal model approach in this context 49 . Of course, involvement of various other pathways cannot be excluded, including inflammatory pathways and oxidative stress pathways involving in ceramide-induced vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…(39) Pathway analysis on the predicted targets of these miRs strongly implicated RUNX2, toll-like receptors, and mechanotransduction as key downstream pathological effectors of vascular EVs, while valvular EV miRs were linked to IL-17 and sphingolipid signaling pathways that are involved in valvular inflammatory cell infiltration and osteogenesis/calcification. (40)…”
Section: Discussionmentioning
confidence: 99%